Revitalisasi Pendampingan Ibadah berbasis Nilai Sosial Keagamaan bagi ODGJ Level 4 dalam Mendukung Proses Rehabilitasi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This community service program aims to revitalize religious and social-value-based worship services for people with mental disorders (ODGJ) level 4 to support the rehabilitation process at the Sidoarjo Regency Social Service. ODGJ level 4 are individuals with mild mental disorders who still have the potential to develop socially and spiritually if they receive appropriate support. However, in practice, the rehabilitation program tends to focus on medical and psychological aspects, while spiritual guidance has not been optimally integrated. The implementation method uses a participatory approach involving companions, families, and the social environment under the coordination of the Sidoarjo Regency Social Service. The results of the activity indicate that the revitalization of religious and social-value-based worship services can increase the involvement of ODGJ in worship activities, improve social interactions, and have a positive impact on the emotional stability of participants. In addition, this program also encourages the active role of families and communities in supporting the spiritual-based rehabilitation process. Thus, the approach worship assistance based on socio-religious values ​​can be an alternative model in supporting the holistic rehabilitation of ODGJ level 4, which includes spiritual, social, and psychological aspects, especially in the context of community-based services at the Sidoarjo Regency Social Service.